Paradigms of knowledge and neomodernity: The relevance of Mario Osorio Marques' proposal (Revista Contexto & Educação, 2025)
The legacy of Mário Osório Marques leaves us, among many other valuable contributions, the notion of paradigms of knowledge and reason – ontological, modern subjective and intersubjective – in the human tradition. This paper traces a path of bibliographical review and hermeneutical source that disagrees on each paradigm proposed by the author, as well as a transition between them. Marques enables the tension between each paradigmatic moment and the presence, limitations and possibilities of education in the conception of truth, positioning himself, after a linguistic turn, in the paradigm of communicative reason, which enables the conception of neomodernity, a term coined by Rouanet. Thus, neomodernity is proposed as a paradigmatic position capable of thinking about the problem of knowledge, education/learning and the implications of this for the social dimension of the world. The neomodern paradigmatic positioning and intersubjective reasoning represent the possibility of escaping the civilizing and emancipatory potential of the Enlightenment, in the face of a context of relativism, fake news and authoritarianism, that is, what Marques called a context of “systematically disturbed, asymmetrical and manipulative communication”.
Keywords: Paradigms; neomodernity; knowledge; school